Prolonged Gestation due to Mummified Fetuses in Conjunction with Normal Fetus in Barbari Doe - Mahajan, Mohit; Prasad, Shiv; Singh, Vipin; Tevatia, Gourav S.; Verma, Prashant (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The hypothalamus pituitary adrenal axis of the fetus is the prime pathway for initiation of parturition and corticotropin-releasing factor (CRF) plays a central role in the stress response for regulating this axis. Lefebvre (2015) revealed pathological conditions such as mummification, maceration, mucometra, hydrometra and pyometra altered the normal function of the hypothalamic pituitary adrenal axis, prolonging gestation and alternating the normal physiology of the dam. Mummification is a sequel of foetal death without abortion, often after ossification of bones, and the resorption of the fetus is unfeasible (Noakes et al., 2009; Chaudhari and Dabas, 2018). The incidence of mummification (4%) is reported to be the highest among other gestational disorders (Vikram et al. 2020) and is rarely recorded in does and ewes. Mummification is associated with four major infectious causes Toxoplasmosis, Chlamydophila, Border disease (Pestivirus) and Coxiella Brunetti (Edmondson et al., 2012; Lefebvre, 2015). Non-infectious causes of mummification include traumatic injury to the fetus (Broaddus et al. 2009; Dubey 2009), umbilical cord compression (Mahajan and Sharma, 2002), uterine torsion, defective placentation (Irons, 1999), genetic anomalies, abnormal hormonal profiles and chromosomal abnormalities. Protein and energy deficiency during advance gestation may lead to fatal mummification with animals clinically appearing weak and anemic (Lefebvre, 2015).